Social Media Misinformation Effect on Mental Health in Covid-19: A Review Study - Sijariya, Rajeev; Roy, Chandreyee; Jindal, Lokesh; Sharma, Yogesh; Suri, Ankit (Journal of Commerce and Trade, 2022)
Mental health is a global concern in the current era, which has also been prioritized as one of the sustainable development goals. The impact of COVID-19 was not only limited to physical health; it also affected the individuals psychologically. According to the statistics, individuals were busy sparing time in social media regardless the accuracy of the content, which lead to misinformation effect. Misinformation effect was one of the serious issues faced by the individuals at the time of COVID 19. Anxiety, stress, depression, fears are the symptoms reported by the individuals. This paper attempts to contribute the literature regarding the social media misinformation effect on mental health in COVID-19. Further studies can also be done based on the psychological impact of misinformation effect from an Indian perspective that will also help to develop the social networking initiative for promoting health services and public safety. Classification-JEL: I12 Acknowledgement The scholar namely Dr. Rajeev Sijariya is the awardee of ICSSR Research Project. This paper is largely an outcome of the Research Project “Triple Bottom line approach for resilient recovery and resurgence amid Covid 19:- An Eco-Social Psychological framework for Bharat 5.0 in new normal”, sponsored by the Indian Council of Social Science Research (ICSSR). However, the responsibility for the facts stated, opinions expressed, and the conclusions drawn is entirely that of the authors.